ELT materials transformed: Exploring outcome-based education elements in high school EFLtextbooks - Pulungan, Anni Holila; Jasni Kharisma, Adib; Kusmanto, Joko; Ginting, Pirman (English Language Teaching Educational Journal, 2024)
Infusing outcome-based components such as advanced communication, productivity and accountability, critical thinking, creativity, collaboration, and flexibility and adaptability are deemed critical in a textbook. Conversely, the evidence revealed shortcomings in certain aspects of textbooks, as exemplified by the "Bahasa Inggris Kelas XII" textbook, which was deficient in advanced teamwork and communication skills. This research endeavor seeks to assess how the textbook incorporates outcome-based education. Utilizing data on the text unit order, the current study employed a descriptive qualitative research framework and acquired data through a Likert scale. The findings disclose that various aspects of outcome-based education are thoroughly addressed in this textbook. Nonetheless, the collaborative component and the intricate communication aspect are conspicuously absent as denoted in chapter 3 and chapter 4. A mere forty-seven percent of the content in the textbook "Bahasa Inggris Grade XII" has been assessed and meets the criteria of outcome-based education. This level of attainment, which falls below expectations, indicates a lack of complete adherence to the principles of outcomes-based education within the English textbook. As this ongoing research carries significant implications for those involved in developing and writing curricula. It is recommended that the textbook aligns with Spady's concept of Outcome-Based Education (OBE), addressing gaps such as the lack of emphasis on teamwork and complex communication aspects. To enhance the achievement of educational objectives, authors are advised to pinpoint areas for enhancement through collaboration with educators, students, and curriculum experts.